Weed management options for improving yield and economics of pigeonpea in Odisha - Panda, P.K.; Kar, A.; Panigrahi, R.K. (Annals of Agricultural Research, 2018)
A field experiment was conducted during kharif season of 2014-15 and 2015-16 at the Centre for Pulses Research , OUAT, Berhampur to identify suitable integrated weed management technology and optimize proper herbicide combination for pigeonpea. Nine treatments viz. T1: Weedy check, T2: Pendimethalin 750 g/ha + Hand weeding/ inter culture at 50 DAS, T3: EPOE Imazethapyr 75 g/ha at 15 DAS + HW/IC at 50 DAS, T4: EPOE Imazethapyr 75 g/ha at 10 DAS + Quizalofop ethyl 50 g/ha at 15 DAS, T5: Tank mix application of Imazethapyr 75 g/ha + Quizalofop ethyl 50 g/ha at 15 DAS, T6: T4 + HW/IC at 50 DAS, T7: T5 + HW/IC at 50 DAS, T8: Pendimethalin 750 g/ha + EPOE Imazethapyr 60 g /ha at 15 DAE of weeds and T9: Weed free check , were tested in Randomised Block Design. The growth and yield attributes of pigeonpea were significantly affected by weed management practices. Among the treatments, the lowest weed density and weed dry matter (WDM) along with the highest weed control efficiency (WCE) at 30, 50 & 70 DAS were recorded in T7 , which was very close to the weed free check. Yield attributes like, number of primary fruiting branches/plant, number of pods/plant, number of seeds/pod were maximum in T7 and ultimately the highest grain yield (1278 kg/ha) was recorded in T7( Tankmix of imazethapyr 75 g/ha & quizalofop ethyl 50 g/ha +HW). However, the highest B:C ratio (3.51) was registered with T8 , despite the highest net return (Rs. 37127/ha) obtained from T7.